Chemical toxic exposures and chronic ocular pain - Graca, Mateusz; Sarantopoulos, Konstantinos; Horn, Danielle Bodzin (Frontiers in Toxicology, 2023)
Chronic ocular pain is a common, debilitating chronic pain condition with significant morbidity and negative impact in patients’ quality of life. Several, diverse types of insults to the ocular surface can lead to acute, and under certain conditions to chronic ocular pain, and these include toxic irritants. Exposure of ocular surface to toxic irritants, in addition to direct tissue injury, carries the capacity to generated intense immune and neuronal responses with hyper-excitability, sensitization and chronic pain. Because, chronic ocular pain subsequent to toxic exposures is relatively unrecognized clinical entity, this brief review highlights pertinent concepts of its epidemiology, pathogenesis/pathophysiology, clinical progression, with recommendations for its clinical management that clinicians may find helpful. Suppression of pain signaling, generating neuronal sensitization, and prevention of chronicity of neuropathic pain is particularly emphasized in this respect.